КАРНЕВАЛСКА СЛИКА СВЕТА У РОМАНИМА НА ДРИНИ ЋУПРИЈА И ТРАВНИЧКА ХРОНИКА (Philological Studies, 2019)
: In this work the topic which will be discussed is the carnival image of the world in the novels The Bridge on the Drina and The Days of the Consuls (Bosnian Story), written by Ivo Andric. At first, we will consider the importance of collective scenes with a special review on holiday atmosphere on one side, and the atmosphere of rebellion and protest on the other side. We will discuss the carnival characteristics such as deposal and dethronement as well as leading ideologies. We will pay attention especially to the figure of a fool, and after that to material, physical and grotesque images. The subject we will interpret is the connection of Andric’s novels with the carnival vision of death and birth. As a realistic writer whose framework is in a permanent tie with history and tradition, Ivo Andric gives us a pretext for thinking and considering in this way. The wealth and variety of the collective scenes, the limited field of action, personal and historical experiences of time as well as the characters of eccentrics in Andric’s plays give the form to the characteristic carnival world. Noting the carnival will be further considered not only in its basic meaning (like a folk street festival) but as a special experience of the world as well.
Keywords: Mikhail Bakhtin, Ivo Andric, carnival, grotesque realism, inversion, ambivalence, detronization, desacralization, parody